A Protein Kinase Cε/Protein Kinase D3 Signalling Axis Modulates RhoA Activity During Cytokinesis - Ursula Braun; Michael Leitges (Biomedicines)
Background: Protein kinase D3 (PKD3) is a member of the PKD family that has been implicated in many intracellular signalling pathways. However, defined statements regarding PKD isoform specificity and in vivo functions are rare. Methods: Here, we use PKD3-depleted mouse embryonic fibroblast cells and employ various cell culture-based assays and fluorescence microscopy. Results: We show that PKD3 is involved in the regulation of cytokinesis after immortalisation by modulating RhoA activity through a PKCε/PKD3 signalling axis. Conclusions: PKD3 depletion leads to prolonged RhoA activity during cytokinesis, resulting in failed abscission and an increase in the number of multinucleated cells. This identifies a novel, previously unrecognised PKCε/PKD3 pathway involved in the modulation of cytokinesis.